Effects of combined 17β-estradiol and progesterone on weight and blood pressure in postmenopausal women of the REPLENISH trial. Issue 1 (January 2021) - Black, Denise R.; Minkin, Mary Jane; Graham, Shelli; Bernick, Brian; Mirkin, Sebastian
Abstract: Objective: To examine the impact of a single-capsule 17β-estradiol (E2)/progesterone (P4) on weight and blood pressure (BP) when treating moderate to severe vasomotor symptoms in postmenopausal women with a uterus. Methods: Healthy postmenopausal women with a uterus (aged 40-65, body mass index ⩽34 kg/m 2, BP ⩽140/90 mm Hg) were randomized to daily E2/P4 (mg/mg; 1/100, 0.5/100, 0.5/50, 0.25/50) or placebo in the phase 3 REPLENISH trial (NCT01942668). Changes in weight and BP from baseline to month 12 were evaluated. Potentially clinically important changes were defined as increases or decreases from baseline in weight by ≥15% and ≥11.3 kg, systolic BP by ≥20 mm Hg (absolute value ≥160 or ⩽90 mm Hg), and diastolic BP by ≥15 mm Hg (absolute value ≥90 or ⩽60 mm Hg). Results: Overall mean changes in weight and BP from baseline to month 12 with E2/P4 were modest and generally not statistically or clinically significant versus placebo. Incidence of potentially clinically important changes was low for weight (E2/P4 vs placebo: 1.1-2.6% vs 2.2%), systolic BP (0.3-1.1% vs 1.1%), and diastolic BP (1.4-4.2% vs 3.2%). A small number of women had treatment-related, treatment-emergent adverse events of weight gain (1.4-2.6% vs 1.3%) or hypertension (0.2-1.2% vs 0%). Few women who discontinued E2/P4 had weight gain (1.6%) or hypertension (0.6%) as a primary reason. Efficacy profile on VMS was consistent with previous findings and not modified by body mass index. Conclusions: Twelve-month use of E2/P4 had no clinically meaningful impact on weight or BP in postmenopausal women of the REPLENISH study.